2016
DOI: 10.1177/0190272516643052
|View full text |Cite
|
Sign up to set email alerts
|

Status Characteristics and Ability Attributions in Hungarian School Classes

Abstract: We study how the status characteristics gender and ethnicity affect the abilities that adolescents attribute to each other in the Hungarian school context. For this, we derive predictions from status characteristics theory that we test by applying exponential random graph models to data collected among students in 27 school classes. By that, we contribute to the few existing studies of status characteristics in a school context, and we propose a novel approach to handle structural dependencies between individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…There is no clear evidence that educational tasks are considered either masculine or feminine. Grow et al (2016), for instance, found no significant gender differences in ability perceptions among Hungarian adolescents. Several other studies suggest, however, that boys are more likely to be perceived as competent in educational settings as well (e.g., Correll, 2001;Goddard Spear, 1984;Grunspan et al, 2016).…”
Section: Double Standards In Evaluationmentioning
confidence: 88%
See 4 more Smart Citations
“…There is no clear evidence that educational tasks are considered either masculine or feminine. Grow et al (2016), for instance, found no significant gender differences in ability perceptions among Hungarian adolescents. Several other studies suggest, however, that boys are more likely to be perceived as competent in educational settings as well (e.g., Correll, 2001;Goddard Spear, 1984;Grunspan et al, 2016).…”
Section: Double Standards In Evaluationmentioning
confidence: 88%
“…Friendship. Previous research showed that students are more likely to nominate their friends as clever than to nominate classmates who are not their friends (Grow et al, 2016). Moreover, Foschi (2000) proposed that positive and negative sentiments (e.g., like and dislike) can affect performance expectations and competence standards.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations